2021
DOI: 10.1097/dss.0000000000003005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial of the Latest Generation of Noninvasive Monopolar Radiofrequency for the Treatment of Facial and Upper Neck Skin Laxity

Abstract: BACKGROUND Aging of the face and upper neck is a complex process characterized by loss of collagen and elastic fibers, resulting in clinical skin laxity. Noninvasive interventions such as monopolar capacitively coupled radiofrequency (MRF) have gained popularity, offering a safer and more convenient alternative to traditional surgical face lift. The latest MRF device features larger tips, vibration, cooling, and impedance matching. OBJECTIVE We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Alhaddad et al [14] demonstrated that MRF significantly improved cheek laxity, nasolabial folds, jowls, and upper neck laxity as early as 30 days after the procedure. Furthermore, Angra et al [2] showed that 80% and 73% of subjects improved by months 3 and 6, respectively. In the current investigation, we observed greater degrees of improvement at the 3-and 6-month follow-ups, and more moderate-to-marked improvements were seen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alhaddad et al [14] demonstrated that MRF significantly improved cheek laxity, nasolabial folds, jowls, and upper neck laxity as early as 30 days after the procedure. Furthermore, Angra et al [2] showed that 80% and 73% of subjects improved by months 3 and 6, respectively. In the current investigation, we observed greater degrees of improvement at the 3-and 6-month follow-ups, and more moderate-to-marked improvements were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Angra et al. [ 2 ] showed that 80% and 73% of subjects improved by months 3 and 6, respectively. In the current investigation, we observed greater degrees of improvement at the 3- and 6-month follow-ups, and more moderate-to-marked improvements were seen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations